Effect of nitrogen doping in amorphous carbon thin films grown by Thermal Chemical Vapor Deposition (CVD) method: article / Maisarah Mohd Robat - Mohd Robat, Maisarah (2012)
Thin films of amorphous carbon with different nitrogen flow rates were deposited on quartz substrate by Thermal Chemical Vapor Deposition (CVD) technique. Camphor oil was used as the precursor while argon and nitrogen were used as carrier gas. The electrical, optical and structural properties were characterized by using Bukoh Keiki (CEP2000) Solar Simulator system at room temperature, Perkin Elmer (LAMBDA 750) UV/Vis spectroscope, Raman spectroscope and Atomic ForceAtomic XE-100 PARK SYSTEM Microscope (AFM) respectively. There are significant changes in conductivity (dark and illumination), optical bandgap and structural properties when Nitrogen doping was introduced and the flow rate was varied .Nitrogen flow rate of 30 bubbles per minute sample gives the highest value of conductivity, absorption coefficient and intensity and have a narrow band gap.